2016
DOI: 10.1007/s13278-016-0345-x
|View full text |Cite
|
Sign up to set email alerts
|

Close communication and 2-clubs in corporate networks: Europe 2010

Abstract: Corporate networks, as induced by interlocking directorates between corporations, provide structures of personal communication between their boards. This paper studies such networks using the framework of a previous paper by Laan et al. (Soc Netw Anal Min, 2016. doi:10. 1007/s13278-016-0326-0) where close communication is defined by sub-networks, so that each pair of nodes (boards of a corporation) are either neighbours or have at least one common neighbour. These correspond to sub-graphs of diameter at most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A subgraph whose vertices are all distance at most s is called an s-club (notice that, when s = 1, an s-club is exactly a clique). The identification of s-clubs inside a network has been defined for the analysis of networks [21,1] and has been recently applied for the analysis of social networks [20,22,27], and biological networks [23,3]. Interesting recent studies have shown the relevance of finding s-clubs in a network [20,22], in particular focusing on finding 2-clubs in real networks like DBLP or a European corporate network.…”
Section: Introductionmentioning
confidence: 99%
“…A subgraph whose vertices are all distance at most s is called an s-club (notice that, when s = 1, an s-club is exactly a clique). The identification of s-clubs inside a network has been defined for the analysis of networks [21,1] and has been recently applied for the analysis of social networks [20,22,27], and biological networks [23,3]. Interesting recent studies have shown the relevance of finding s-clubs in a network [20,22], in particular focusing on finding 2-clubs in real networks like DBLP or a European corporate network.…”
Section: Introductionmentioning
confidence: 99%